Thermal and Electrical Properties of Carbon Nanotube Based Materials - Yuca, N.; Karatepe, N.; Yakuphanoğlu, Fahrettin; Gursel, Y. H. (Polish Acad Sciences Inst Physics, 2013)
In this study, carbon nanotubes were synthesized at temperatures of 500 degrees C and 800 degrees C by the fluidized-bed chemical vapor deposition method. The synthesized material was purified by using 3 M HCl at 75 degrees C, 15 h. After synthesis and purification, the polyaniline-doped H3BO3 and BF3 and composites were prepared by coagulation method. Transmission electron microscope and Fourier transform infrared spectroscopy were used to characterize the carbon nanotubes and their composites. Thermal stabilities were measured by thermogravimetry and differential scanning calorimetry instruments. The thermogravimetry and derivative thermogravimetry curves indicated that the thermal stability of polyaniline-doped H3BO3 and BF3 increased with carbon nanotube doping. The electrical properties of carbon nanotubes and their composites were also determined. The obtained electrical conductivity values of the nanocomposites including the polyaniline-doped H3BO3 and BF3 were typical for organic semiconductor materials. It can be evaluated that the electrical properties of the polyaniline based polymers can be controlled by carbon nanotube doping. DOI: 10.12693/APhysPolA.123.352
2nd International Congress on Advances in Applied Physics and Materials Science (APMAS) -- APR 26-29, 2012 -- Antalya, TURKEY
Keywords: Composite